2007
DOI: 10.1073/pnas.0700523104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory factors associated with anaphase-promoting complex/cylosome in mitotic checkpoint

Abstract: The mitotic (or spindle assembly) checkpoint system ensures accurate chromosome segregation by preventing anaphase initiation until all chromosomes are correctly attached to the mitotic spindle. It affects the activity of the anaphase-promoting complex/cyclosome (APC/C), a ubiquitin ligase that targets inhibitors of anaphase initiation for degradation. The mechanisms by which this system regulates APC/C remain obscure. Some models propose that the system promotes sequestration of the APC/C activator Cdc20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 35 publications
5
91
1
Order By: Relevance
“…When such extracts were incubated in the presence of ATP, APC/C was converted to an active form following a lag period. This process was accompanied by the release of inhibitory factors from APC/C and the disassembly of MCC (8,9). We found that the hydrolysis of ATP at the β−γ position was required for both for the activation of APC/C and for the disassembly of MCC (10); this was different from the previously described requirement of checkpoint inactivation for ubiquitylation (11,12), because the latter process involves the cleavage of the α−β bond of ATP (13).…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…When such extracts were incubated in the presence of ATP, APC/C was converted to an active form following a lag period. This process was accompanied by the release of inhibitory factors from APC/C and the disassembly of MCC (8,9). We found that the hydrolysis of ATP at the β−γ position was required for both for the activation of APC/C and for the disassembly of MCC (10); this was different from the previously described requirement of checkpoint inactivation for ubiquitylation (11,12), because the latter process involves the cleavage of the α−β bond of ATP (13).…”
contrasting
confidence: 53%
“…Extracts from nocodazole-arrested HeLa cells were prepared as described previously (9). To isolate MCC free of APC/C, extracts were subjected to sequential immunoprecipitations with anti-Cdc27 followed by anti-BubR1 antibodies [both bound to Affi-Prep Protein A beads (Bio-Rad)], as described (10,17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 4, in sham-depleted extract cyclin B was degraded after a lag, as described (9,23). In TRIP13, p31 comet double-depleted extract, there was little degradation of cyclin B after 3 h of incubation.…”
Section: Resultsmentioning
confidence: 91%
“…The MCC may also bind to APC in a kinetochore independent manner to eventually inhibit APC by releasing O-Mad2, forming the stable Bub3:BubR1:Cdc20:APC complex. The recently discovered mitotic checkpoint factor 2 protein (MCF2) is a highly potent APC inhibitor, yet the mechanism of binding to the APC and its regulation is still elusive (Braunstein et al, 2007;Eytan et al, 2008). All complexes inhibiting APC (except of MCF2) rely on the presence of Cdc20:C-Mad2, which requires unattached kinetochores for adequately fast formation.…”
Section: Apc Inhibitionmentioning
confidence: 99%